LncRNA OLMALINC promotes osteosarcoma progression through USP1-mediated autophagy suppression - Jianping Li; Bo Yu; Zhaowen Xue; Yiping Liang; Shanchuang Chen; Tao Gui; Zitao Liu; Lei Zhang; Rui Peng (Human Cell, 2025)

CircTBCK protects against osteoarthritis by regulating extracellular matrix and autophagy - Wei Wang; Yuzhe Sun; Peng Tang; Rui Zhang; Yufeng Jiang; Hongwei Min; Chen Gao (Human Cell, 2025)
Osteoarthritis (OA) is a widespread chronic bone and joint disease for which there is currently no effective preventive or therapeutic treatment. Accumulating evidence indicates that circular RNAs (circRNAs), a class of noncoding RNAs, play critical roles in OA. Therefore, in this study, we aimed to reveal an unexplored circTBCK and elucidate its mechanism of action in the pathological process of OA. The different expression of circTBCK was obtained both in vitro and in vivo. In the in vivo model, mice were induced via destabilization of the medial meniscus (DMM) surgery, while in vitro model, mouse cells like primary chondrocytes of newborn mice and ATDC5 cell line were treated with IL-1β treatment (10 ng/mL for 24 h). The level of circTBCK was examined by quantitative real-time polymerase chain reaction (qRT-PCR). After circTBCK was overexpressed or knocked down, IL-1β treatment was performed, and then, chondrocyte viability was detected via a Cell Counting Kit-8 (CCK-8) assay at 0, 24, 48, or 72 h. To assess type II collagen (Collagen II) expression, immunofluorescence (IF) analysis was used. The levels of mRNAs and proteins related to proliferation, the extracellular matrix (ECM) and autophagy were determined by qRT-PCR and Western blotting. Compared with OA treatment, primary chondrocytes with treatment of both circTBCK overexpression and IL-1βincreased the expression of anabolic factors—Collagen II and SRY-box transcription factor 9 (SOX9), proliferation-related molecules—Ki-67 and proliferating cell nuclear antigen (PCNA), and autophagy-related molecules—Microtubule-associated protein 1 light chain 3 (LC3), B-cell lymphoma 1 (Bcl1), and autophagy-related 5 (Atg5) and decreased Sequestosome 1 (SQSTM1 or P62). In contrast, knockdown of circTBCK aggravated the chondrocyte degeneration induced by IL-1β. Overall, our findings suggest that circTBCK, an unexplored circRNA, could regulate autophagy, proliferation, and the extracellular matrix (ECM) to mitigate the development of OA, suggesting a possible target for OA prevention and therapy.

TEAD4 predicts poor prognosis and transcriptionally targets PLAGL2 in serous ovarian cancer - Xin Tong; Yi-Si Liu; Rui Tong; Wei-Wei Tang; Xue-Mei Li; Chun-Yan Wang; Yong-Peng Wang (Human Cell, 2023)

MiR-100-5p inhibits osteogenic differentiation of human bone mesenchymal stromal cells by targeting TMEM135 - Rui Wang; Miao Zhang; Ying Hu; Juan He; Qiao Lin; Nianchun Peng (Human Cell, 2022)

Erratum to: Glycogen synthase kinase 3 (GSK3)-inhibitor SB216763 promotes the conversion of human umbilical cord mesenchymal stem cells into neural precursors in adherent culture - Liyang Gao; Mingyan Zhao; Peng Li; Junchao Kong; Zhijun Liu; Yonghua Chen; Rui Huang; Jiaqi Chu; Juanhua Quan; Rong Zeng (Human Cell, 2017)

Glycogen synthase kinase 3 (GSK3)-inhibitor SB216763 promotes the conversion of human umbilical cord mesenchymal stem cells into neural precursors in adherent culture - Liyang Gao; Mingyan Zhao; Peng Li; Junchao Kong; Zhijun Liu; Yonghua Chen; Rui Huang; Jiaqi Chu; Juanhua Quan; Rong Zeng (Human Cell, 2017)